PEMANFAATAN MEDIA ULAT BULU DALAM MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DI TK TRISULA 01 PERWARI SINGOSARI - Fitria Agung Rizki; Mohammad Afifulloh; Eko Setiawan (Jurnal Dewantara, 2021)
The problem encountered in Trisula Perwari Singosari Kindergarten is the lack of teacher stimulus for children to relax paper by squeezing, flattening, touching, on their fingers. The purpose of this study was an activity of squeezing newspapers into the shape of a caterpillar to improve fine motor skills in children at Trisula 01 Perwari Kindergarten. The research method used is classroom action research (CAR). The research subjects were 21 children. The results of the discussion in the pre-cycle cycle are: (29%) because children experience delays in moving their fingers. And there was an increase in cycle I (62%) because the child was able to move his fingers in squeezing newsprint. Then the researcher continued the second cycle (86%) because the children were able to relax.